"Stainomics": Identification of mitotracker labeled proteins in mammalian cells. Issue 13 (2nd July 2013) - Dong, Hongjuan; Cheung, Sau Ha; Liang, Yimin; Wang, Baojiang; Ramalingam, Rajkumar; Wang, Ping; Sun, Hongyan; Cheng, Shuk Han; Lam, Yun Wah
<x xml:space="preserve">Abstract</x> Organelle‐specific cell‐permeable fluorescent dyes are invaluable tools in cell biology as they reveal intracellular dynamics in living cells. Mitrotracker is a family of dyes that strongly label the mitochondrion, a key organelle associated with many crucial cellular functions. Despite the popularity of these dyes, little is known about the molecular mechanism behind their staining specificity. Here, we aimed to identify the protein targets of one member of this dye family, mitotracker red (MTR), by 2DE and MS. MTR bound to cellular proteins covalently, and its fluorescence persisted even after cell lysis, protein solubilization, denaturation, and electrophoresis. This enabled us to display MTR‐labeled proteins by 2DE. The MTR‐specific fluorescent signals on the gel revealed the spots that contained MTR‐conjugated proteins. These spots were analyzed by MS, resulting into the identification of ten proteins. We discovered that one major target is the mitochondrial protein HSP60 and that MTR staining could induce production of HSP60, predisposing cells to heat shock‐like responses. The identification of the molecular targets of biological dyes, or "stainomics, " can help correlate their intracellular staining properties with biochemical affinities. We believe this approach can be applied to a wide range of fluorescent probes.